2021
DOI: 10.1111/evo.14217
|View full text |Cite|
|
Sign up to set email alerts
|

Constrained sex allocation after mating in a haplodiploid thrips species depends on maternal condition

Abstract: In females of haplodiploid animals, female production requires fertilization, whereas male production does not. Therefore, haplodiploid species can display extraordinary sex ratios. Constrained sex allocation occurs when a female cannot produce daughters. This can be due to virginity but may also occur after mating due to insemination failure, selfish genetic elements or physiological constraints. Here, we investigated the mechanism underlying constrained sex allocation in Pezothrips kellyanus. In this species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 87 publications
3
13
0
Order By: Relevance
“…Offspring sex ratio of each individual female was calculated as the percentage of male offspring in the brood. Consistent with a previous study (Katlav et al 2021a ), females showed a bimodal sex ratio pattern and were thus grouped into two categories depending on the percentage of male offspring: constrained females with 85–100% male offspring (M broods) and unconstrained females with 0–15% male offspring (F broods). Due to the bimodal nature of sex allocation in this species, a mixed effects logistic regression was used to analyse the effect of “infection status” and “temperature” (as two binary fixed factors; infected vs. uninfected; 20 vs. 25 °C) on the probability of constrained sex allocation.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…Offspring sex ratio of each individual female was calculated as the percentage of male offspring in the brood. Consistent with a previous study (Katlav et al 2021a ), females showed a bimodal sex ratio pattern and were thus grouped into two categories depending on the percentage of male offspring: constrained females with 85–100% male offspring (M broods) and unconstrained females with 0–15% male offspring (F broods). Due to the bimodal nature of sex allocation in this species, a mixed effects logistic regression was used to analyse the effect of “infection status” and “temperature” (as two binary fixed factors; infected vs. uninfected; 20 vs. 25 °C) on the probability of constrained sex allocation.…”
Section: Methodssupporting
confidence: 86%
“…We further hypothesize that the increased male production at the higher temperature may be due to an increase in constrained sex allocation. We have previously found that constrained sex allocation in P. kellyanus is linked with lower fertilization rates (Katlav et al 2021a ). Therefore, increased constrained sex allocation may prevent the expression of CI (which is only ever manifested in fertilized embryos of haplodiploid hosts).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations